2015
DOI: 10.1111/infa.12107
|View full text |Cite
|
Sign up to set email alerts
|

How to Foster Toddlers' Mental‐State Talk, Emotion Understanding, and Prosocial Behavior: A Conversation‐Based Intervention at Nursery School

Abstract: Recent years have seen the development and implementation of a range of training programs aimed at improving children's socio‐emotional skills. Nevertheless, few studies have been conducted with toddlers attending nursery school. In this study, we adopted observational and experimental paradigms to examine the efficacy of an intervention based on conversing about emotions with small groups of 2‐ to 3‐year‐old children. The intervention was designed to promote toddlers' mental‐state talk, emotion understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 51 publications
3
32
0
3
Order By: Relevance
“…Interestingly, the positive effect was found to remain stable over time. Similar results were recently found by Grazzani et al (2016) in a study with toddlers, showing that EC plays a crucial role in the development of even the earliest prosocial behavior.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the positive effect was found to remain stable over time. Similar results were recently found by Grazzani et al (2016) in a study with toddlers, showing that EC plays a crucial role in the development of even the earliest prosocial behavior.…”
Section: Introductionsupporting
confidence: 89%
“…In line with the outcomes of a large number of studies with preschoolers (e.g., Eisenberg et al, 2006 ; Eggum et al, 2011 ; Ornaghi et al, 2015 ), which have shown that EC is a key indicator and predictor of prosociality from early childhood, we found that participants’ EC and prosocial orientation were highly positively correlated. Additional evidence for this link comes from recent intervention studies showing that training young children in EC skills (such as understanding the expression and causes of emotion or the fact that emotions may be regulated) fosters their disposition to behave prosocially toward others and helps them to better recognize and understand other people’s emotional states and needs ( Aram and Shlak, 2008 ; Ornaghi et al, 2015 ; Grazzani et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, we have carried out studies in which a small group of children listened to a short story from an illustrated storybook developed ad hoc by our research team and containing reference to a range of inner states. We have found that even training 2-year-old children in using mental-state talk during conversation in small groups had a significant effect on their language ability and social cognition (Grazzani et al 2016b;Grazzani et al 2016a). These early childhood education contexts, which remain as yet under-researched, appear to be particularly rich sociocultural ecotopes or small developmental units of language and social cognition.…”
Section: Resultsmentioning
confidence: 93%
“…, (Sales, Fivush, & Peterson, 2003;Van Bergen & Salmon, 2010), , (Ruffman, Slade, Devitt, & Crowe, 2006;Thompson & Winer, 2014), (Wang & Fivush, 2005), (Wang & Fivush, 2005), (Thompson & Winer, 2014) . , Ornaghi, Agliati, & Brazzelli, 2016;Ornaghi, Pepe, & Grazzani, 2016). (Brownell, Svetlova, Anderson, Nichols, & Drummond, 2013;Thompson & Winer, 2014), (Laible & Thompson, 2000).…”
Section: Introductionmentioning
confidence: 99%